2020
DOI: 10.21815/jde.019.163
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers to Academic Success for International Students Studying Dental Hygiene in the U.S

Abstract: The number of international students coming to the U.S. for post‐secondary education has been steadily increasing. Prior research has found that international students encounter many barriers to academic success, but this topic has not been previously studied for the discipline of dental hygiene. The aims of this study were to investigate the barriers and challenges to academic success faced by international students in U.S. dental hygiene programs and to explore the students’ thoughts on the value they bring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Bektaş (2009) states that international students choose their friends either from their own country or the host country to help them to adjust and cope with difficulties. Research studies have examined the relationship between acculturation and psychological adjustment, and it has been shown that acculturation is related to psychological adjustment (Jenkins & Boyd, 2020;Liu, 2015;Schneider et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Bektaş (2009) states that international students choose their friends either from their own country or the host country to help them to adjust and cope with difficulties. Research studies have examined the relationship between acculturation and psychological adjustment, and it has been shown that acculturation is related to psychological adjustment (Jenkins & Boyd, 2020;Liu, 2015;Schneider et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Acculturative stress negatively shapes the physical and psychological health and well-being of international students (Al- Krenawi et al, 2020;Dorevitch et al, 2020;Jenkins and Boyd, 2020;Liu et al, 2020;Minutillo et al, 2020), a phenomenon that could be further exacerbated by global crises such as international trade wars and the COVID-19 pandemic (Ma and Miller, 2020;Su et al, 2020;Zhai and Du, 2020;Zheng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Acculturative stress negatively shapes the physical and psychological health and well-being of international students ( Al-Krenawi et al, 2020 ; Dorevitch et al, 2020 ; Jenkins and Boyd, 2020 ; Liu et al, 2020 ; Minutillo et al, 2020 ), a phenomenon that could be further exacerbated by global crises such as international trade wars and the COVID-19 pandemic ( Ma and Miller, 2020 ; Su et al, 2020 ; Zhai and Du, 2020 ; Zheng et al, 2020 ). However, there is a lack of research that sheds light on the intensity, impacts, and consequences of acculturative stress on international students’ health and well-being, particularly those of Chinese origin.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative research has been used to gain feedback on dental education courses, and this has been obtained using either questionnaire or interview-based approaches. [9][10][11] The aim of the present teaching review was to obtain feedback from graduates of the TCD Orthodontic Therapy course. For this study, a focus group was the chosen method to obtain feedback from past course participants.…”
Section: Introductionmentioning
confidence: 99%